1987
DOI: 10.1111/j.1432-1033.1987.tb11199.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of barley chymotrypsin inhibitor‐2 (CI‐2) and its expression in normal and high‐lysine barley

Abstract: cDNA clones for chymotrypsin inhibitor-2 (CI-2) have been isolated from an endosperm-specific library of barley using a synthetic oligonucleotide probe. The nucleotide sequences of several of the cDNAs predict an open reading frame (beginning with an ATG codon) which encodes a protein of 84 residues (Mr 9380). In the longest clone another ATG codon is present, a further 69 nucleotides upstream. The nucleotide sequence between these two ATG codons predicts an amino acid sequence with the characteristics of a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 46 publications
3
44
1
Order By: Relevance
“…4B) and the synthesis of an immunologically related polypeptide encoded by a locus on chromosome 7 [9] [33] and thionins [36] are all synthesized in the developing endosperm and are coded for by small multigene families. Of these the Hor2 locus on chromosome 5, the gene family encoding B-hordein polypeptides, has been studied in detail.…”
Section: Discusslonmentioning
confidence: 99%
See 1 more Smart Citation
“…4B) and the synthesis of an immunologically related polypeptide encoded by a locus on chromosome 7 [9] [33] and thionins [36] are all synthesized in the developing endosperm and are coded for by small multigene families. Of these the Hor2 locus on chromosome 5, the gene family encoding B-hordein polypeptides, has been studied in detail.…”
Section: Discusslonmentioning
confidence: 99%
“…5). Among the chymotrypsin inhibitors, CI-2 is synthesized without a cleavable signal peptide, but has an internal hydrophobic sequence [33] and is transported via the Golgi apparatus to the vacuole of the cell [34]. Like protein Z4, P-amylase is synthesized in the mature form [lo] on membrane-bound polysomes [I 61.…”
Section: Discusslonmentioning
confidence: 99%
“…Note the high content of lysine residues (K) and absence of cysteine. Based on data in Williamson et al (1987Williamson et al ( , 1988. Standard single letter abbreviations for amino acids are used.…”
Section: Nutritional Qualitymentioning
confidence: 99%
“…Since no other experimental evidence is available to support that this protein is an ACP, it is suggested that henceforth the name ACP IlI be used for the pACP 1 coded protein. Figure 4 reveals that the poly A signal (38) at bases 656-661 (numbers correspond to pACP 11 in Figure 4), in contrast to those in the other two cDNAs, is followed 56 bases later by a tail of at least 51 adenines. The open reading frame translating into 49 amino acids in the 3' region lacks the consensus initiation sequence.…”
Section: Pacpmentioning
confidence: 99%